Antimicrobial susceptibilities of oral Neisseria from men on HIV pre-exposure prophylaxis in Hanoi, Vietnam - Huan Vinh Dong; Paul Adamson; Dieu Hoa Pham; Quynh Hoa Pham; Hai Ha Long Le; Loc Quang Pham; Hao Thi Minh Bui; Giang Minh Le; Jeffrey D. Klausner (Journal of Global Antimicrobial Resistance)
ABSTRACT: Background: Antimicrobial resistance (AMR) in Neisseria gonorrhoeae (N. gonorrhoeae) is an urgent global health concern. Commensal Neisseria species in the oropharynx are an important reservoir of AMR genes that are transferred to N. gonorrhoeae, yet few data about AMR among commensal Neisseria in populations at risk for AMR exist. Methods: From May 2022 to December 2023, men in an HIV pre-exposure prophylaxis program in Hanoi, Vietnam, were recruited for this study. Participants self-collected oral specimens using phosphate buffer solution, for culture on LB agar media containing sucrose, vancomycin, and trimethoprim (LBVT.SNR). Oxidase-positive Gram-negative diplococci were identified using the Remel RapID NH system. Minimum inhibitory concentrations (MICs) to azithromycin, ceftriaxone, cefixime, and doxycycline were determined using Etests. Results: There were 42 male participants, the median age was 26 years and 29% (n = 12) reported using antibiotics in the past 6 months. In total, 48 Neisseria isolates were recovered; N. sicca/subflava was the most common species (50%; n = 24), followed by N. mucosa (38%; n = 18). For azithromycin, 85% (n = 41) of isolates were resistant with MICs ≥ 1 ug/mL, including 25% (n = 12) with high-level resistance (MICs ≥ 256 ug/mL of which 67% (8/12) were N. mucosa. Among non-gonococcal Neisseria isolates, the prevalence of resistance was 6% (n = 3) for ceftriaxone, 6% (n = 3) for cefixime, and 54% (n = 26) for doxycycline; the most non-susceptible isolates were N. mucosa. Conclusions: A High frequency of azithromycin resistance, moderate doxycycline resistance, and low cephalosporin resistance was found in oropharyngeal Neisseria isolates from men who have sex with men (MSM) in a pre-exposure prophylaxis (PrEP) program in Hanoi, Vietnam. N. mucosa was over-represented among resistant isolates.